Sustainable practices proactivity: an analysis of practices of Mercur S.A. - Alves, Ana Paula Ferreira; Nascimento, Luis Felipe Machado do (Revista de Administração da UFSM, 2016)
The adoption of sustainable practices in companies can be analyzed in a continuous, consisting of two extremes: the reactive and proactive response. In this context, sustainable proactivity can be defined as the adoption of actions carried out voluntarily by companies, in order to improve the environmental and social performance and social, beyond legal requirements. A proactive company states their concern and their commitment to society and the environment in which it operates. Given these considerations, this research aims to analyze the voluntary adoption of sustainable practices – sustainable proactivity – of a company. Therefore, a case study was performed with the company Mercur S.A. The results indicate that Mercur can be considered a proactive company, according to the full implementation of actions for sustainability at the core business of the organization and the partial implementation of other practices. Furthermore, the sustainable proactive behavior of Mercur can stimulate their partners, contributing to the introduction of sustainability practices in other companies.